Reabilitação do coberto lenhoso ribeirinho nas margens da Lagoa dos Linhos, Mata Nacional do Urso - Fabião, André (2022)
To test the viability of riparian cover restoration using common methods of forestation, afield trial consisting on installation of riparian species was performed at Lagoa dos Linhos (Urso National Forest). The species utilized were: Quercus faginea, Q. robur, Salix atrocinerea, Crataegus monoggyna, Populus nigra, Tamarix africana, Acer campestre and A. monspessulanum. Quercus faginea and A. campestre were planted (pure and mixed compositions) and directly sown (pure composition), whereas the remaining species were all planted with mixed composition.Survival and growth were monitored during 34 months, allowing the conclusion that the installation method (sowing or plantation) influenced the survival of A. campestre, which did not succeed in the sown area.